Size Effects in Ruthenium-Based Thick-Film Resistors: Rutile vs. Pyrochlore-Based Resistors - M. Prudenziati; F. Sirotti; M. Sacchi; B. Morten; A. Tombesi; T. Akomolafe (Active and Passive Electronic Components)
The size effect, namely the change of sheet resistance, Rs as a function of resistor length, has been investigated in layers whose conductive phase evolves from Pb-rich (Ru-deficient pyrochlores) to Pb2Ru2O6.5 and finally to RuO2 by increasing the firing temperature. It is found that Bi diffusion from the terminations is responsible for lower sheet resistance values in shorter resistors whatever the conductive phase is. On the contrary, Ag diffusion is responsible for lower sheet resistance values in shorter resistors only in the case of ruthenate conductive grains while the reverse is observed in RuO2-based layers. Size effect can be suppressed with Pt/Au-based terminations provided that no Bi is contained and with Au-metallorganic-based contact provided that the peak firing temperature is not too high.